Правова природа припинення договору про патронат - Лешанич, Леся Вікторівна; Лешанич, Леся Викторовна; Leshanych, Lesya V. (My University, 2015)
Дитяча безпритульність являється досить актуальною проблемою сьогодення. Договір про патронат має досить давню історію існування. Відомо, що історія нашої країни розвивалась дуже динамічно і українські землі на певних етапах державного становлення входили до складу різних країн. Можливо, така ситуація і призвела до низького рівня законодавчого врегулювання відносин патронату над дітьми, в тому числі, і відносин, котрі виникають з приводу розірвання, припинення договору про патронат.

Детская беспризорность является достаточно актуальной проблемой.Договор о патронате имеет достаточно давнюю историю существования.Известно,что история нашей страны развивалась очень динамично и украинские земли на определенных этапах государственного становления входили в состав разных стран.Возможно,такая ситуация и привела к низкому уровню законодательного урегулирования отношений патроната над детьми, в том числе,и отношений,которые возникают по поводу расторжения,прекращения договора о патронате.

Child homelessness is a very relevant issue of the day.It is known that orphanages although they contribute to the solving of the problem of child homelessness, but they do not bring up orphans and children deprived of parental care in the spirit of full readiness for adult life, while familial and quasifamilial forms of upbringing of a child make it possible to create all the conditions for a comprehensive, complete moral and spiritual development of a child. Along with familytype children’s home and foster family, a patronage agreement is one of the quasi familial forms of upbringing of orphans and children deprived of parental care. According to the Article 252 of the Family Code of Ukraine (hereinafter the FC of Ukraine), under the patronage agreement, the Custody and Care Authority transfers an orphan or a child deprived of parental care to another person’s family (a patron) for upbringing the child for payment until the child reaches adult status. The FC of Ukraine provides grounds for suspension and termination of the agreement of patronage. The author of the article believes that this list of grounds for suspension and termination of the agree ment of patronage is not exhaustive. The agreement of patronage has quite a long history of existence. It is known that the history of our country de veloped very dynamically and that at certain stages of the formation of the state Ukrainian lands formed parts of different countries. It is possible that this situation has led to the low level of legislative regulation concerning relations of patronage of children,including as well the relations that arise over the cancellation, termination of the agreement of patronage.
Лешанич Л. В. Правова природа припинення договору про патронат / Л. В. Лешанич // Часопис цивілістики. – 2015. – Вип. 18. – С. 73-76.
Keywords: припинення договору; розірвання договору; патронат; договір про патронат; окремі види зобов’язань; прерывание договора; расторжение договора; патронат; договор о патронате; отдельные виды обязательств; termination of the contract; denounce a treatment; foster care; contract of foster care; certain types of obligations